Multiple nuclear localization sequences in SRSF4 protein. (25th February 2020) - Masaki, So; Kabuto, Takafumi; Suzuki, Kenji; Kataoka, Naoyuki
Abstract: SRSF4 is one of the members of serine‐/arginine (SR)‐rich protein family involved in both constitutive and alternative splicing. SRSF4 is localized in the nucleus with speckled pattern, but its nuclear localization signal was not determined. Here, we have identified nuclear localization signals (NLSs) of SRSF4 by using a pyruvate kinase fusion system. As expected, arginine‐/serine (RS)‐rich domain of SRSF4 confers nuclear localization activity when it is fused to PK protein. We then further delineated the minimum sequences for nuclear localization in RS domain of SRSF4. Surprisingly, RS‐rich region does not always have a nuclear localization activity. In addition, basic amino acid stretches that resemble to classical‐type NLSs were identified. These results strongly suggest that SRSF4 protein uses two different nuclear import pathways with multiple NLSs in RS domain. Abstract : SRSF4 is a splicing factor that belongs to serine‐/arginine‐rich (SR) protein splicing factor family. By using reporter protein system, we have identified nuclear localization signals (NLSs) of SRSF4. It was assumed that arginine‐/serine‐rich (RS) domain of SRSF4 confers its nuclear localization activity. However, we found that SRSF4 has not only RS repeat‐type NLSs but also classical‐type NLSs. These results strongly suggest that SRSF4 protein uses two different nuclear import pathways with multiple NLSs in RS domain.